2014
DOI: 10.1007/s12195-014-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Pressure During Fluid Flow Regulates Purinergic Signaling and Cytoskeleton Organization of Osteoblasts

Abstract: During physiological activities, osteoblasts experience a variety of mechanical forces that stimulate anabolic responses at the cellular level necessary for the formation of new bone. Previous studies have primarily investigated the osteoblastic response to individual forms of mechanical stimuli. However in this study, we evaluated the response of osteoblasts to two simultaneous, but independently controlled stimuli; fluid flow-induced shear stress (FSS) and static or cyclic hydrostatic pressure (SHP or CHP, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Moreover, this ATP release was magnitude depedent over time at each loading event. To date, only osteoblasts have been shown to elicit an ATP response to CHP, whereas, stem cells were found to secrete ATP in a fluid flow magnitude dependent manner [ 44 46 ]. Purinergic signalling plays a crucial role in bone anabolism, therefore ATP synthesis in response to mechanical stimulation may highlight initiation of mechanotransduction events, irrespective of type of stimulus [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this ATP release was magnitude depedent over time at each loading event. To date, only osteoblasts have been shown to elicit an ATP response to CHP, whereas, stem cells were found to secrete ATP in a fluid flow magnitude dependent manner [ 44 46 ]. Purinergic signalling plays a crucial role in bone anabolism, therefore ATP synthesis in response to mechanical stimulation may highlight initiation of mechanotransduction events, irrespective of type of stimulus [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs express P2X as well as P2Y receptors, and are shown to have high ATP signaling activity on their cell surface [ 37 – 40 ]. Previously, we reported that shear stress upregulated the P2Y 2 receptor in HUVECs [ 12 , 41 ] and recent studies from others have suggested that these receptors mediate mechanotransduction [ 14 , 15 , 26 ]. Our primary findings in the present study are that P2Y 2 receptors modulate endothelial cell alignment, ASF formation, and cell migration in HUVECs and we thereby propose a novel role for P2Y 2 receptors in shear stress-induced endothelial cell remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that endothelial cells release ATP and UTP, in response to various stimuli including hypoxia, vascular injury, and mechanical stimulation, and that these extracellular nucleotides act as paracrine or autocrine mediators via activation of purinergic P2 receptors [ 9 , 10 ]. Purinergic receptors are classified into P2X ligand-gated ion channel receptors and P2Y G protein-coupled receptors [ 11 ] and among these receptors, the P2X4 receptor is implicated in flow-induced calcium flux, vasodilation, and atheroprotective gene expression [ 12 , 13 ] while the P2Y 2 receptor is associated with mechanosensitivity in osteoblasts [ 14 , 15 ]. Both ATP and/or UTP are shown to influence endothelial cell cytoskeletal changes such as actin filament formation and cell motility, associated with activation of integrins and growth factor receptors [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it remains elusive how cells can sense hydrostatic pressure in the first place, as the molecular nature of a potential pressure sensor is still unknown. There is some evidence for Ca 2+ , purinergic signaling, RhoA, Rac1 and NF-KB being involved in the adaption to changes in ambient (the background; ∼760 mmHg, 101 kPa) pressure (Gardinier et al, 2014;Mandal et al, 2010;Sappington et al, 2009;Zhao et al, 2015). However, these messenger ions/signaling molecules are likely downstream targets of the actual pressure sensor.…”
Section: Introductionmentioning
confidence: 99%